Future of Multimedia: Mixed Reality in Virtual 3D Exhibitions and Digital Products - Padmasari, Ayung Candra; Bin Azizan, Ahamad Tarmizi; Fadli, Muhammad Nur; Salsabila, Rifda Falsa (Jurnal Pendidikan Multimedia (Edsence), 2024)
Creative digital application products are currently expanding rapidly and become the base of many countries to compete in the global market, including in Indonesia, which is preparing the creative economy of the digital application development subsector as a new force in the post-Covid 19 national economic recovery, especially in the focus of achieving the Sustainable Development Goals (SDGs). In the 2020 Game Industry Ecosystem Map report, it is known that 57% of the 80 surveyed digital application development companies said that productivity has declined since the pandemic, with the emergence of a new variation of Covid 19 type Omicron appearing at the beginning of 2022, making the impact of the epidemic on the industry huge. Therefore, the government has made a policy to carry out the recovery jointly through the Programme Strategy (RPJMN) of the National Medium-term Development Plan 2020-2024 (SDGs, Objective 4 Quality Education), on the Development Programme of innovative study programmes adapted to the needs of development and industry, with a partnership strategy of universities and industry for curriculum alignment, development of curricula, research and development activities. The method used in the research is MDLC (Multimedia Development Life Cycle). In this study, 1 virtual 3D exhibition building was produced with 6 rooms consisting of a game and application media room, a digital illustration room, an industrial partnership room accompanied by an interactive navigation design based on Mixed Reality.